'They will attach themselves to the House of Jacob': A redactional study of the oracles concerning the nations in the Book of Isaiah 13-23 - Lee, J (2015)
The present study argues that a series of programmatic additions were made to the oracles concerning the nations in Isa 13-23 during the late-exilic period by the same circle of writers who were responsible for Isa 40-55. These additions were made to create continuity between the ancient oracles against the nations from the Isaiah tradition and the future fate of the same nations as the late-exilic redactor(s) foresaw. The additions portray a two-sided vision concerning the nations. One group of passages (14:1-2; 14:32b; 16:1-4a; 18:7) depicts a positive turn for certain nations while the other group of passages (14:26-27; 19:16-17; 23:8-9, 11) continues to pronounce doom against the remaining nations. This double-sided vision is set out first in Isa 14 surrounding the famous taunt against the fallen tyrant. 14:1-2, before the taunt, paints the broad picture of the future return of the exiles and the attachment of the gentiles to the people of Israel. After the taunt and other sayings of YHWH against his enemies, 14:26-27 extends the sphere of the underlying theme of 14:4b-25a, namely YHWH’s judgement against boastful and tyrannical power(s), to all nations and the whole earth. The two sides of this vision are then applied accordingly to the rest of the oracles concerning nations in chs 13-23. To the nations that have experienced similar disasters as the people of Israel, words of hope in line with 14:1-2 were given. To the nations that still possessed some prominence and reasons to be proud, words of doom in line with 14:26-27 were decreed. Only later in the post-exilic period, for whatever reason, be it changed international political climate or further spread of the Jewish diaspora, was the inclusive vision of 14:1-2 extended even to the nations that were not so favourably viewed by our late-exilic redactor (19:18-25; 23:15-18).